Quill for Teaching Writing of Recount Text in Senior High School - Mahendra, Sillvy Dwy Putri Diana (RETAIN, 2022)
The aims of this research were to find out whether the use of Quill application for teaching writing can improve the students' writing skills or not. Moreover, this study intends to describe the students’ responses toward the implementation of Quill application to teach writing for tenth-grade students of SMAN 1 Dawarblandong. The researcher used pre-experimental research. The participants were tenth-grade students in SMAN 1 Dawarblandong. The other data were collected from observation, tests, and interviews. The result indicated that teaching writing using the Quill application improved the students' writing skills. In addition, the result of the interview showed the students’ response of the implementation of Quill application in teaching and learning writing recount text. The advantages and disadvantages of implementing the Quill application were found based on the observation and interview.